Road Safety Go to School: Sosialisasi Keselamatan Berlalu Lintas pada Siswa SMA Witama Srikandi Pekanbaru - Anggraini, Muthia; Haris, Virgo Trisep; Masrul, Wati (Jurnal Pengabdian KOLABORATIF, 2026)
Road traffic safety is a fundamental aspect that should be instilled from an early age, particularly among senior high school students, many of whom are already active road users. The Road Safety Go to School program was implemented as an educational initiative to enhance students' knowledge, awareness, and compliance with traffic safety regulations. The program was conducted at Witama Srikandi Senior High School, Pekanbaru, using educational lectures, awareness campaigns, and interactive discussions. The learning materials covered the importance of road traffic safety, recognition of traffic signs and traffic signal lights (APILL), safe road-use practices, and safe riding principles. The results indicated a substantial improvement in students' understanding of road traffic safety. Based on the post-program questionnaire, all 80 participants (100%) demonstrated an adequate understanding of the topics presented. Prior to the educational intervention, 58.75% of participants were unfamiliar with the concept of safe riding, 56.26% lacked knowledge of road traffic safety, and 40.00% were unable to recognize traffic signs and traffic signal lights. Following the program, all participants showed improved knowledge and understanding of these topics. These findings demonstrate that the Road Safety Go to School program was effective in increasing students' awareness and knowledge of road traffic safety, thereby supporting the development of safer traffic behavior among young road users.
Keywords: Road Safety; Safe Riding Principles; Students; Traffic Safety; Traffic Signal Light